Numerical simulation of water injection and pilot analysis in LT reservoir of P oilfield in Ecuador - Li, Jun (2025)
The LT layer of the P oilfield in Ecuador is in the late stage of depletion development. The main production areas have serious formation energy voidage and the production is declining rapidly. In view of this situation, based on the fine geological modeling constrained by seismic amplitude, a numerical simulation study on water injection for energy supplement was carried out. The water injection mode, water injection rate, injection-production ratio and well pattern optimization were studied by using the existing producer to converting injector. The study shows that injector in the low position has better oil recovery than injector in the high position. The water injection volume of 2000-4000 STB/D can be determined according to the on-site injection situation, and the injection-production ratio is more appropriate to be controlled at about 1. The pilot showed that the average daily injection volume was about 3000 barrels, after 8 months of injection, oil production increased from three surrounding wells. This study provides solid technical theory and practical experience guidance for the next step of expanding water injection to the whole area of the P oilfield.